A common fixed point theorem for a sequence of fuzzy mappings - B. E. Rhoades (International Journal of Mathematics and Mathematical Sciences)
We obtain a common fixed point theorem for a sequence of fuzzy mappings, satisfying a contractive definition more general than that of Lee, Lee, Cho and Kim [2].